The Use of Phages and Aptamers as Alternatives to Antibodies in Medical and Food Diagnostics - Mehta, Jaytry; Dorst, Bieke Van; Devriese, Lisa; Rouah-Martin, Elsa; Bekaert, Karen; Somers, Klaartje; Somers, Veerle; Scippo, Marie-Louise; Blust, Ronny; Robbens, Johan (IntechOpen, 2011)
None